Perception Of Teachers Towards On-Line Education With Specific Context To Hospitality Education In India ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: On-line education in a way was a forced introduction in our education system  in wake of COVID-19 pandemic. Teachers as well as students became a part of this shift in  education delivery mostly by force and rather by choice. However, in the short run itself it  was realised that while shifting to this new-medium has its own challenges it also comes with  its own set of advantages. Objective: This research paper attempts to study and analyse the  perception of teachers in hospitality education towards on-line education. Objective of study  is to identify the major challenges and benefits of hospitality education as perceived by faculty  members. Methodology: Descriptive research design was employed. The study was conducted  by administering a structured questionnaire among faculty members of various IHMs and  analysis of data was done. Locale is pan-India reached through google questionnaire method  with a sample size of 50 faculty members from different IHMs in the country. Data was  analysed with the help of excel tools, bar diagrams and graph. Results: Research revealed  that in spite of the sudden paradigm shift in the macro environment faculty members responded  well to the challenge of optimising learning for students in an on-line mode. Initially 80 %  faculty members found this shift challenging but now 80 percent believe that blended learning  is future. Assessments and sustaining interest of students however are major challenges with  82 and 84 percent of faculty members respectively agreeing to this being a major issue.  Conclusion: Teachers perceive blended learning to be a norm in future. It is perceived that  while it’s very difficult to impart skill training in an on-line mode, for theoretical classes this  could be a preferred mode
Keywords: Online Education; Hospitality Education; Challenges; Advantages